2018
DOI: 10.1002/joc.5445
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term variability of the cloud amount and cloud genera and their relationship with circulation (Kraków, Poland)

Abstract: The article demonstrates the impact of atmospheric circulation on the long‐term variability of cloudiness (amount and certain cloud genera) in Kraków based on midday observations of the amount and genera of clouds in the period from 1 January 1906 to 31 December 2015. There was found statistically significant (although rather moderate) correlation between circulation indices and the frequency of cloud cover consisting of a single cloud genus or a group of clouds. The 11‐year moving averages of frequency of occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Based on the conducted analysis, it was found for all months that the correlation between atmospheric circulation type and area‐average monthly SD is stronger for the type of pressure system than for the direction of air mass advection (Figure 7). A similar relationship was found for other climate elements in Poland, for example, for cloud cover and precipitation (Twardosz and Niedźwiedź, 2001; Matuszko and Węglarczyk, 2018). The area‐average monthly SD in Poland show a strong statistically significant relationship with the type of pressure system, that is, positive in anticyclonic situations and negative in cyclonic situations (Figure 7).…”
Section: Discussion Of the Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…Based on the conducted analysis, it was found for all months that the correlation between atmospheric circulation type and area‐average monthly SD is stronger for the type of pressure system than for the direction of air mass advection (Figure 7). A similar relationship was found for other climate elements in Poland, for example, for cloud cover and precipitation (Twardosz and Niedźwiedź, 2001; Matuszko and Węglarczyk, 2018). The area‐average monthly SD in Poland show a strong statistically significant relationship with the type of pressure system, that is, positive in anticyclonic situations and negative in cyclonic situations (Figure 7).…”
Section: Discussion Of the Resultssupporting
confidence: 75%
“…After 1990, there was another increase in the cyclonicity index and a slight increase in cloud cover over the entire decade, followed by a several-year decrease and another increase by 2010. The beginning of the second decade of the 21st century indicates a further decline in the cyclonicity index and a weakening of the zonal circulation with the western component, while there was an increase in the meridional circulation with the southern circulation, reaching a maximum in 2014 (Matuszko and Węglarczyk, 2018).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is only one known study relating cloud distribution to synoptic circulation (Sanchez‐Lorenzo et al ., ). On an international level, more studies can be found on atmospheric patterns affecting cloud cover (Rmillard and Tselioudis, ; de Szoeke et al ., ; Matuszkoa and Weglarczyk, ; Mechem et al ., ). Therefore, a comprehensive study of cloudiness using data collected from the Moderate Resolution Imaging Spectroradiometer (MODIS) instrument aboard the Terra and Aqua satellites has been carried out relating it to the classification of local‐regional synoptic patterns.…”
Section: Introductionmentioning
confidence: 99%